Changing forces of gravity: How the crisis affected international banking - Claudia M. Buch; Katja Neugebauer; Christoph Schröder (Institut für Angewandte Wirtschaftsforschung (IAW), 2013)
The global financial crisis has brought to an end a rather unprecedented period of banks' international expansion. We analyze the effects of the crisis on international banking. Using a detailed dataset on the international assets of all German banks with foreign affiliates for the years 2002-2011, we study bank internationalization before and during the crisis. Our data allow analyzing not only the international assets of the banks' headquarters but also of their foreign affiliates. We show that banks have lowered their international assets, both along the extensive and the intensive margin. This withdrawal from foreign markets is the result of changing market conditions, of policy interventions, and of a weakly increasing sensitivity of banks to financial frictions.
Keywords: G01; F34; G21; 330; International banking; gravity model; financial frictions